BMP7-induced osteoblast differentiation requires hedgehog signaling and involves nuclear mechanisms of gene expression control - Feltran, Georgia da Silva [UNESP]; de Andrade, Amanda Fantini [UNESP]; Fernandes, Célio Jr da C. [UNESP]; da Silva, Rodrigo A. Foganholi [UNESP]; Zambuzzi, Willian F. [UNESP] (Wiley, 2024)
During the morphological changes occurring in osteoblast differentiation, Sonic hedgehog (Shh) plays a crucial role. While some progress has been made in understanding this process, the epigenetic mechanisms governing the expression of Hh signaling members in response to bone morphogenetic protein 7 (BMP7) signaling in osteoblasts remain poorly understood. To delve deeper into this issue, we treated pre-osteoblasts (pObs) with 100 ng/mL of BMP7 for up to 21 days. Initially, we validated the osteogenic phenotype by confirming elevated expression of well-defined gene biomarkers, including Runx2, Osterix, Alkaline Phosphatase (Alp), and bone sialoprotein (Bsp). Simultaneously, Hh signaling-related members Sonic (Shh), Indian (Ihh), and Desert (Dhh) Hedgehog (Hh) exhibited nuanced modulation over the 21 days in vitro period. Subsequently, we evaluated epigenetic markers, and our data revealed a notable change in the CpG methylation profile, considering the methylation/hydroxymethylation ratio. CpG methylation is a reversible process regulated by DNA methyltransferases and demethylases, including Ten-eleven translocation (Tets), which also exhibited changes during the acquisition of the osteogenic phenotype. Specifically, we measured the methylation pattern of Shh-related genes and demonstrated a positive Pearson correlation for GLI Family Zinc Finger 1 (Gli1) and Patched (Ptch1). This data underscores the significance of the epigenetic machinery in modulating the BMP7-induced osteogenic phenotype by influencing the activity of Shh-related genes. In conclusion, this study highlights the positive impact of epigenetic control on the expression of genes related to hedgehog signaling during the morphogenetic changes induced by BMP7 signaling in osteoblasts.
Keywords: BMP; bone; bone healing; epigenetic; hedgehog; osteoblast differentiation